High‐resolution multibeam sonar bathymetry of the deepest place in each ocean. (5th May 2021) - Bongiovanni, Cassandra; Stewart, Heather A.; Jamieson, Alan J.
Abstract: Over the course of 10 months, the global Five Deeps Expedition (2018–2019) mapped 550, 000 km 2 of seafloor of which 61% comprised new coverage over areas never before surveyed and 30% was acquired from some of the ocean's deepest trenches and fracture zones. The deepest points of each ocean were mapped using a latest‐generation, full‐ocean depth Kongsberg EM 124 multibeam echosounder. These extreme depths were corrected using Conductivity, Temperature and Depth (CTD) data from sea surface to full ocean depth. The deepest place in each ocean were identified as the Brownson Deep, Puerto Rico Trench in the Atlantic Ocean (8, 378 ± 5 m), an unnamed deep within the South Sandwich Trench in the Southern Ocean (7, 432 ± 13 m), an unnamed deep within the Java Trench in the Indian Ocean (7, 187 ± 13 m), Challenger Deep within the Mariana Trench in the Pacific Ocean (10, 924 ± 15 m), and the Molloy Hole in the Arctic Ocean (5, 551 ± 14 m). As part of the overarching mission of the Five Deeps Expedition, and to clarify beyond doubt the deepest point in the Indian, Pacific and Southern oceans, other sites were visited that had been postulated as potential deepest locations. This study has confirmed that the Horizon Deep within the Tonga Trench is the second deepest point in the Pacific Ocean (10, 816 ± 16 m), the Dordrecht Deep within the Diamantina Fracture Zone is not the deepest point in the Indian Ocean (7, 019 ± 17 m) and that in accordance with the guidelines of the Antarctic Treaty and International Hydrographic Organisation, although the Meteor Deep is the deepest point in the South Sandwich Trench (8, 265 ± 13 m) it is located within the waters of the Atlantic Ocean and not the Southern Ocean. Abstract : Using the GEBCO_2019 bathymetric data complication's source information, all interpolated data sources were removed to show the true extent of publicly available global bathymetry. Red circles indicate the deepest points in the five oceans surveyed during the Five Deeps Expedition. Red line displays the ship's mapping route between dive locations.